(3QSGdI cTa GdMbGFbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe GdMeO deYfi GdeYGfi QH GdeSei hGdGSe hGdTcQ ddYdi GdCYdi NGdb GdQhM s
(3BNQgG (B:s
(3dGjhUa HGddSGf hdGJOQc HGdLfGf GdhGMO GdCMO GdefJbe ef GdeTQcjf HSja ehdGfG hMOg hTOg SdWGfg JeJ GdQSGdI HMeO ehdGfG hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds